2003
DOI: 10.1046/j.1525-142x.2003.03032.x
|View full text |Cite
|
Sign up to set email alerts
|

A DM domain protein from a coral, Acropora millepora, homologous to proteins important for sex determination

Abstract: The identification and functional studies of DM domain-containing proteins Doublesex, MAB-3, and DMRT1 indicated that flies, nematodes, and humans share at least some of the molecular mechanisms of sex determination. We identified a gene, AmDM1, from the coral Acropora millepora that encodes a homologous DM domain-containing protein. Molecular analyses show that the AmDM1 primary transcript is processed to generate four different messenger RNAs. Alternative use of two polyadenylation sites produces transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Unlike those DMRT1 homologues that had been characterized for their genomic organizations Miller et al, 2003;Raymond et al, 2000;Sreenivasulu et al, 2002;Xu et al, 2005), no introns were found in the ORF of grouper DMRT1 by the genomic sequence analysis, and this finding were further confirmed by several control experiments to rule out the contamination possibility ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 54%
“…Unlike those DMRT1 homologues that had been characterized for their genomic organizations Miller et al, 2003;Raymond et al, 2000;Sreenivasulu et al, 2002;Xu et al, 2005), no introns were found in the ORF of grouper DMRT1 by the genomic sequence analysis, and this finding were further confirmed by several control experiments to rule out the contamination possibility ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 54%
“…Amino acid alignments showed that the DM domain shares 98% identity with that of Drosophila Dmrt99B and vertebrate Dmrt5, but outside the DM domain, there is little sequence homology between them. Furthermore, the short consensus of 7aa RSAFSPI and the other conserved domain DMA specific to the Dmrt99B and Dmrt3-5 (Miller et al 2003;Ottolenghi et al 2002) are also not found in the crab Dmrt (Fig. 1b).…”
Section: Resultsmentioning
confidence: 95%
“…Dmrt genes have rarely been identified in other invertebrate species (Miller et al 2003;Naimi et al 2009). Recently, three DM domain genes were cloned in a small pelagic crustacean Daphnia magna and revealed to be sexually dimorphic gene expression (Kato et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the realization that sexual dimorphism is ancient, dating back to the last common ancestor of coelomate bilaterians, posed a problem in light of how diverse the genetic control of sex specification is known to be [Haag and Doty, 2005]. And it was the finding of the DM gene family across vertebrates and invertebrates [Raymond et al, 1998[Raymond et al, , 1999Miller et al, 2003] showing that their sex determining mechanisms may derive from a shared common ancestor that helped to solve this apparent dilemma [Haag and Doty, 2005]. A similar question about homology and common ancestry relates to the sex chromosome systems found in vertebrates (XY or ZW).…”
Section: Discussionmentioning
confidence: 99%